Progress in cognition of gas-solid interface reaction for non-oxide ceramics at high temperature. Issue 3 (4th May 2021) - Wang, Enhui; Hou, Xinmei; Chen, Yafeng; Fang, Zhi; Chen, Junhong; Liang, Tongxiang; Chou, Kuo-chih; Nickel, Klaus G.
Abstract: With the progress in science and technology, non-oxide ceramics (NOCs) are playing a vital role in various fields at high temperature. However, under harsh service conditions, NOCs tend to be confronted with complicated interface reactions with different media, leading to an acceleration in material failure. Among which, the gas-solid reaction is the most common one accompanied by the highest reaction rate, and the corresponding principles and methods are always applicable to solid-solid and liquid-solid reactions. Therefore, deep understanding of the gas-solid interface reaction behavior is significantly important. Herein, contemporary aspects of gas-solid interface reaction of NOCs are reviewed to show how efficient different approaches are to understand the reaction behavior and mechanism. This review covers theoretical approaches based on kinetic models, experimental approaches using advanced instruments as testing and characterization techniques, and simulative approaches with the help of first-principle calculation and molecular dynamics. Different kinetic models applied to different reaction types are introduced and compared, which have a unique advantage in describing and predicting the gas-solid interface reaction behavior of NOCs. Various techniques are illustrated to show the intuitive observation of changes in microstructure and phase composition at the reaction interface. Based on the above two aspects, the effects of external environment on the gas-solid interface reaction are explained and the significance of interface evolution of NOCs themselves is recognized. To reveal the internal reaction essence, the typical application of recently rising simulative approaches is illustrated to show their potentials in observing the reaction path at the atomic and molecular scale and revealing the reaction mechanism. Finally, some research areas worthy being carried out are pointed out. This review will give a deep understanding of the gas-solid interface reaction and provide scientific designing basis for the performance improvement of NOCs.